RATIO DECIDENDI PUTUSAN NO. 119/PDT.SUS-PHI/2019/PN.PBR. TERHADAP PEMUTUSAN HUBUNGAN KERJASAMA ANTARA PEGAWAI DAN PT. MALINDO KARYA LESTARI - Nabil Mahri; Betty Kurnia Rahayu; Mochamad Jazri Aditiya Pranata; Oktafredianus Dede Lisiansu (Jurnal HUKUM BISNIS, 2022)
Malindo Karya Lestari was sued by two people who were formerly employees who worked for the company. ON Law no. 2 of 2004 concerning the Settlement of Industrial Relations Disputes regarding the settlement of labor disputes through the Industrial Relations Court. In this lawsuit is the Work Termination Lawsuit arising from the Termination of Employment Decree issued by the Defendant because the Defendant did not agree with the existence of a labor union in the Defendant's Company so that the Defendant prevented the Plaintiffs from forming or carrying out labor union activities (Union Busting). Termination of Employment due to disputes that arise and have not found a suitability of opinion regarding the final decision of Termination of Employment. Keywords: Employment Relations Decision, Decidendi Ratio